Full-Phase Operation Transresistance-Mode Precision Full-Wave Rectifier Designs Using Single Operational Transresistance Amplifier - Hung-Chun Chien (Active and Passive Electronic Components)
This study proposed the designs of two full-phase operation transresistance-mode (TRM) precision full-wave rectifiers. The first circuit consisted of a single operational transresistance amplifier (OTRA), four diodes, and a resistor. The second scheme was an OTRA combined with a full metal-oxide semiconductor field-effect transistor-based design, which is preferable for integrated circuit implementation because no passive components are used in the circuit topology. Based on our literature review, this is the first study that discussed a full-phase operation transresistance-mode precision full-wave rectifier consisting of a single OTRA and few passive components. In this paper, several previously reported precision full-wave rectifiers consisting of various active devices are first reviewed followed by the proposed OTRA-based transresistance-mode precision full-wave rectifiers and an analysis of nonideal effects. Furthermore, computer simulations and experimental results are presented to verify the validity of the proposed circuits, which were consistent with the theoretical predictions.